Fabrication and gas sensing properties of hollow SnO2 hemispheres - Chang, Young-Eun; Youn, Doo-Young; Ankonina, Guy; Yang, Dae-Jin; Kim, Ho-Gi; Rothschild, Avner; Kim, Il-Doo (ROYAL SOC CHEMISTRY, 2009)
Close packed arrays of hollow SnO2 hemispheres were prepared using PMMA microspheres as sacrificial templates for subsequent sputter-deposition of SnO2 films, leading to a threefold enhancement in gas sensitivity compared to non-templated (flat) films.
Keywords: TITANIA NANOTUBES; SENSORS; SENSITIVITY; MICROSPHERES; HYDROGEN; OXIDES; TEMPLATES; NANOWIRES